Religious belief Systems: Their Ideological Representations and Practical Constraints - Deconchy, Jean-Pierre (The international journal for the psychology of religion, 1991)
Questions that center on ideology and related psychosocial processes bearing on science and religion are critically examined for their relevance to the psychological invariants and cultural characteristics that form the basis of any psychology of religion. It is proposed that a sound phenomenology of the re- ligious differences be identified and that dogmatism, the orthodoxies of spe- cific groups, belief in a just world, and assumptions about what is rational in human behavior be recognized as invariant effects behind the various forms of religion.